Global Influence of American Nursing: some ethical issues - Davis, Anne J (Nursing ethics, 1999)
This article raises some questions about the global influence of nursing in the USA and describes some problems that may come about because of it. Selected American values that are embedded in nursing and ethics are found in American nursing education, practice and research. These can then be exported to countries with very different cultural definitions and values. One such country is Japan. The discrepancy between national cultural norms and imported ideals of nursing practices can create ethical problems for nurses in these countries.